Appraisal of a Learning Coaching Strategy in Rural Areas of Peru in a Results-based Budgeting Rationality - Sempé, Lucas N. (REICE. Ibero-American Journal on Quality, Effectiveness and Change in Education, 2015)
This research analyzes a learning coaching strategy called Acompañamiento Pedagógico promoted by the ministry of Education of Peru since 2008 focusing in rural multi-grade (Spanish and bilingual) schools aiming to improve learning outcomes. It focuses on the learning achievements of its students and also seeks providing advice for improving functioning of the current strategy. The first goal was to determine if there is a significant difference in learning achievements in Spanish reading and comprehension and mathematics between coached and non- coached schools and were performed mixed-designed ANOVAs tests. The finding of statistically significant interactions between receiving coaching for 3-years disclosures an effective strategy in order to increase the goal of any educational system, the learning of students. The second goal of the research was analyzing if the present learning coaching strategy meets the standards set by the national results-based budgeting approach. For that purpose, a documentary review of policy design, focalization and expenditure were performed, finding a design inconsistency, some coverage problems and absence of clear standards and organization parameters.